PENGAWASAN PENGUJIAN KELAYAKAN MOBIL BARANG PADA DINAS PERHUBUNGAN KOTA PEKANBARU TAHUN 2021 - Maulana, Alzis; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In managing the suitability testing of goods cars, the Pekanbaru City Transportation Service has the authority to supervise the suitability of each mandatory test vehicle operated in Pekanbaru City which is carried out by the Motor Vehicle Testing UPTD by carrying out control operations or raids on goods cars. Because apart from providing contributions that are paid to the regional treasury every year, the impact of this supervision is also very important, namely creating social order, safety and comfort in traffic, reducing the number of accidents, improving road sign infrastructure and so on. The aim of this research is to describe the UPTD Supervision of Motor Vehicle Testing at the Pekanbaru City Transportation Service in testing the suitability of goods cars and the obstacles. This research method uses a qualitative method with a case study type of research. The type of research data used in this research is primary data in the form of data and information originating from primary sources and research informants, and secondary data in the form of documents obtained from related documents. The data collection technique in this research is interview and documentation techniques. The findings in this research are that the UPTD supervision of motor vehicle testing at the Pekanbaru City Transportation Service in testing the suitability of goods cars has not been carried out optimally, which is seen from the number of vehicles that are inactive from KIR testing, this is the main focus of the UPTD in its supervision activities. Inhibiting factors include an insufficient budget for carrying out socialization activities regarding SOPs that have been prepared for the community, as well as facilities and infrastructure for testing the suitability of public transport, as well as inadequate human resources. Keywords: Supervision, Goods Car Testing